Arterial Stiffness in Inflammatory Bowel Disease: An Updated Systematic Review and Meta-Analysis - Lu, Qiongqiong; Shi, Rui; Mao, Tangyou; Wang, Zhibin; Sun, Zhongmei; Tan, Xiang; Wang, Yi; Li, Junxiang (Turkish Journal of Gastroenterology, 2021)
Background: This systematic review and meta-analysis were carried out on well-conducted and adequately powered studies to explorewhether arterial stiffness was associated with inflammatory bowel disease (IBD).Methods: The search for potential literature was conducted on PubMed, MEDLINE, Cochrane Library, and Embase from inception toFebruary 15, 2020. The studies assessing arterial stiffness in IBD were reviewed and included.Results: Conclusively, 17 eligible trials with a total of 2188 participants were in compliance with the inclusion criteria. Of the included2188 participants, the cases for ulcerative colitis (UC) and Crohn’s disease (CD) were 558 and 693, respectively. Altogether 10 studieswere conducted to evaluate the carotid-femoral pulse wave velocity (CPWV) in overall IBD patients, which was significantly increasedwith the mean difference (MD) and 95% CI as 0.70 (0.48-0.92, P < .01). The pooled results for CPWV in patients with CD and UC werealso faster than that of control groups with MD and 95% CI as 1.09 (0.45-1.72) and 0.57 (0.57-1.24), respectively. The CPWV in CD andUC groups was comparable with a MD of 0.07 (P = .74, 95% CI: −0.32 to 0.45).Conclusion: Arterial stiffness had associations with the overall IBD, UC, and CD with a similar strength of association between UCand CD.